Evaluation of forest products trade economic contribution by entropy-TOPSIS: Case study of Turkey - Bayram, Bahadır Çağrı (BioResources, 2020)
The forest products industry is one of the most powerful industry branches of Turkey, and as in other developing countries, Turkey has a persistent trade deficit. The present paper aims to evaluate the forest industry products of Turkey regarding their economic contribution by Entropy-TOPSIS, which is a hybrid multicriteria decision making method. The evaluation was done to specify the products which will be able to create currency inflow most for reducing the trade deficit and help economic development. According to computations, the most contributing products are medium-density fiberboard (MDF), high-density fiberboard (HDF), industrial roundwood, and particle board. In addition, household and sanitary papers, as well as other paper and paper board products were found to have great economic potential.
Keywords: 8. Economic growth; 1. No poverty; 15. Life on land